Strengthening communication within the family in anticipating incest behavior in Tanjung Tiram sub-district - Sazali, Hasan (Penerbit Universiti Kebangsaan Malaysia, 2021)
Family communication in a household setting plays an important role in creating a harmonious family, as well as in anticipating the incest behavior of the nuclear family. It is not measured by the quantity load but the value of the meaning of the communication process in the family environment. The research uses a qualitative approach supported by quantitative data in maintaining and strengthening the validity of the research results. The results showed the weak implementation of family communication systems in the community. The values of the religious system, such as the diversity of religions, cultures and social norms also lack positive implications in anticipating incest family behavior. Religious values are only used as symbols in the social system of community life with a high degree of fanaticism. Religious institutions play a less role in anticipating the incest behavior of nuclear families in the community.